The self-annealing phenomenon of electrodeposited nano-twin copper with high defect density - Han, Haneul; Lee, Chaerin; Kim, Youjung; Lee, Jinhyun; Yoon, Sanghwa; Yoo, Bongyoung (Frontiers in Chemistry, 2022)
Electroplated copper was prepared under typical conditions and a high defect density to study the effect of the defects on its self-annealing phenomenon. Two conditions, grain growth and stress relaxation during self-annealing, were analyzed with electron backscattered diffraction and a high-resolution X-ray diffractometer. Abnormal grain growth was observed in both conditions; however, the grown crystal orientation differed. The direction and relative rate at which abnormal grain growth proceeds were specified through textured orientation, and the self-annealing mechanism were studied by observing the residual stress changes over time in the films using the sin2Ψ method.